EVALUATING THE EFFECTIVENESS OF PERFORMANCE MANAGEMENT SYSTEMS TO MOVE TOWARDS BECOME A DIGITAL COMPANYâ: CASE STUDY PT. XYZ - Azmi, Alimah
The era of digitalization requires State-Owned Enterprises (BUMN) in Indonesia to carry out digital transformation. PT. XYZ is a state-owned company engaged in Electronics for Industry and Infrastructure. In order to turn BUMN into a digital company, the Ministry of BUMN has implemented the Seven Elements of Human Capital Architectures to increase competitiveness in the face of current digitalization. One of the architectural elements that is carried is the "Performance Management and Rewarding System". Currently PT. XYZ still uses the traditional performance management system. The pre-survey shows the results that employees feel the current Performance Management System is ineffective due to several factors including non-integrated data, manual processing takes a lot of time only for administrative functions, and does not have a major impact on career development. To become a digital company, BUMN companies are required to be agile and have a digital mindset. This requires PT. XYZ to have a performance management system and corporate culture that leads to digital. Based on the literature, the performance management system is a process that includes planning, designing, implementing, evaluating strategies, performance indicators, and setting targets related to work programs. The management system serves as a strategic, administrative, and development function. Based on the digital cultural framework promoted by CIGREF, the authors adapted this framework to measure the readiness of digital culture and have a PT XYZ performance management system. The seven dimensions measured in the digital culture of PT. XYZ stands for Viability, Openness, Knowledge, Agility, Trust, Interdependence, and Responsibility. Three dimensions measured in the Performance Management System of PT. XYZ stands for Openness, Knowledge, and Agility. Analysis was also carried out on the Compensation System applied at PT. XYZ, which will be used as an additional component in the discussion of the performance management system. From the average results of each dimension obtained from the survey results, the authors flatten each low, medium, and low dimension. From the distribution of this questionnaire, 75 respondents from PT.XYZ obtained from eight divisions and five business units. The survey results show that the readiness of PT XYZ's digital culture is at the medium level with each dimension of Viability, Openness, Knowledge, Agility, Interdependence, and Responsibility being the medium and trust being the only dimension that reaches a high level. The survey also shows that the effectiveness of PT XYZ's performance management system in moving towards a digital company is at a medium level with levels for the dimensions of Openness, Knowledge, Agility as well as medium. The survey on compensation shows the lowest average value on employee satisfaction with the alignment of incentives with the results of performance appraisals. Recommendations for increasing readiness in digital culture are aimed to improve the three lowest dimensions of digital culture: knowledge, agility, and interdependence. The recommendation put forward to improve the effectiveness of the current performance management system is to digitize a performance management system that supports the ii